Strategi Pelayanan Perpustakaan di Masa Pandemi Covid-19 Di Perpustakaan Sekolah SMAN 1 Matauli Pandan Kabupaten Tapanuli Tengah - Suyani Nursiska Sari; Abdul Karim Batubara; Faisal Riza (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2023)
This research discusses service strategies during the Covid-19 pandemic in the School Library of SMAN 1 Matauli Pandan, Central Tapanuli Regency. This research method is descriptive qualitative with data collection techniques in the form of observation, interviews and documentation. The data analysis techniques used are data reduction, data presentation and drawing conclusions. In this research, the research instrument is the researcher himself. The informants were the Matauli Pandan Library manager, library visitors, and several library staff. The results of this research show that the Library Service Strategy of SMAN 1 Matauli Pandan During the Covid-19 Pandemic includes: Washing hands and providing hand sanitizer, library visitors must wear masks, maintain social distancing, library visitors can only be 15 people. only and don't stay too long, library visiting hours are only 08.00-14.00 WIB, extending book borrowing and book return schedules only via WA (Whatsapp), regenerating library users' interest in reading by conducting joint discussion activities, book reviews , and reading books together, as well as other activities carried out virtually. The obstacles faced by librarians and users at the SMAN 1 Matauli Pandan Library during the ongoing Covid-19 pandemic lie in the change in services which were previously carried out face-to-face, to be carried out virtually/online. The solution is to carry out activities in the library virtually/online or search for information that users need through the library's OPAC to reduce the number of visitors who come to the library.